Nations of the Northwest Coast / X - Smithyman, Kathryn, 1961-; Kalman, Bobbie (New York : Crabtree Pub. Co., 2004)
Explores how the waters, mountains, and forests of the Pacific Northwest have provided food and shelter for groups such as the Tlingit, the Haida, and the Kwakiutl for thousands of years.
The Northwest Coast -- Clans, moieties, and phratries -- Villages -- Salmon and cedar -- Homes of the Northwest Coast -- Traveling the waterways -- Trade -- The potlatch ceremony -- Northern peoples -- Central peoples -- Southern peoples -- People from other lands arrive -- Changed ways of life -- The nations today.
Includes index.
Socials
Canada Past
Native people
Keywords: Ward, Donna; Northwoods Press: Canada's Natives Bundle; Indians of North America -- Northwest Coast of North America -- History -- Juvenile literature; Indians of North America -- Northwest Coast of North America -- Social life and customs -- Juvenile literature; Indians of North America -- Northwest Coast of North America